Pola Asuh Makan Sebagai Determinan Status Gizi Anak Usia 12-36 Bulan - Putri Setia Wulandari; Aim Matun Nadhiroh; Awwalul Wiladatil Qodliyah (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2026)
Indonesia faces three burdens of malnutrition, namely overweight and obesity, stunting, and wasting. Nutritional cases are quite higher in the working area of the Jagir Surabaya Health Center. Parenting in feeding is one of the factors that affect the nutritional status of children. This study aims to analyze the relationship between parenting in feeding and the nutritional status of children aged 12–36 months. This study uses a case control design. The sample totaled 66 respondents, consisting of 33 cases with more nutritional status and 33 controls with normal nutritional status. The sampling technique used is purposive sampling. The statistical test used is Chi-Square. The results of the study showed that most parents implemented democratic parenting (72.7%). There was a significant relationship between parenting in feeding and the nutritional status of children aged 12–36 months (p = 0.003). Democratic parenting had a lower risk, which was 0.1 times higher than the quality of nutritional status in children (OR = 0.120; p < 0.001). Permissive parenting increased risk 5.8 times (OR = 5.813; p = 0.021), and authoritarian parenting 7.1 times but was not significant (OR = 7.111; p = 0.105). Democratic parenting tends to support normal nutritional status. Democratic parenting helps children recognize hunger and satiety, while permissiveness encourages overconsumption. Authoritarian patterns can create eating stress and trigger anxiety while eating. There was a meaningful relationship between parenting in feeding and the nutritional status of children aged 12-36 months. Education about proper parenting needs to be improved to support the optimal nutritional status of children.